Symmetry groups of the equations with nonlocal structure and an application for the collisionless Boltzmann equation - Seyidali S., Akhiev; Teoman, Özer (Elsevier BV, 2005)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Rarefied gas flows, Boltzmann equation in fluid mechanics; Nonlinear first-order PDEs; Kinetic theory of gases in time-dependent statistical mechanics; equations with nonlocal structure; collisionless Boltzmann equation; symmetry groups; Geometric theory, characteristics, transformations in context of PDEs